Solve for A A=b(h^2+3h+4)-bh(h+3)-(2h-15)

Math
A=b(h2+3h+4)-bh(h+3)-(2h-15)
Simplify each term.
Tap for more steps…
Apply the distributive property.
A=bh2+b(3h)+b⋅4-bh(h+3)-(2h-15)
Simplify.
Tap for more steps…
Rewrite using the commutative property of multiplication.
A=bh2+3bh+b⋅4-bh(h+3)-(2h-15)
Move 4 to the left of b.
A=bh2+3bh+4⋅b-bh(h+3)-(2h-15)
A=bh2+3bh+4⋅b-bh(h+3)-(2h-15)
Apply the distributive property.
A=bh2+3bh+4b-bh⋅h-bh⋅3-(2h-15)
Multiply h by h by adding the exponents.
Tap for more steps…
Move h.
A=bh2+3bh+4b-b(h⋅h)-bh⋅3-(2h-15)
Multiply h by h.
A=bh2+3bh+4b-bh2-bh⋅3-(2h-15)
A=bh2+3bh+4b-bh2-bh⋅3-(2h-15)
Multiply 3 by -1.
A=bh2+3bh+4b-bh2-3bh-(2h-15)
Apply the distributive property.
A=bh2+3bh+4b-bh2-3bh-(2h)–15
Multiply 2 by -1.
A=bh2+3bh+4b-bh2-3bh-2h–15
Multiply -1 by -15.
A=bh2+3bh+4b-bh2-3bh-2h+15
A=bh2+3bh+4b-bh2-3bh-2h+15
Combine the opposite terms in bh2+3bh+4b-bh2-3bh-2h+15.
Tap for more steps…
Subtract bh2 from bh2.
A=3bh+4b+0-3bh-2h+15
Add 3bh+4b and 0.
A=3bh+4b-3bh-2h+15
Subtract 3bh from 3bh.
A=4b+0-2h+15
Add 4b and 0.
A=4b-2h+15
A=4b-2h+15
Solve for A A=b(h^2+3h+4)-bh(h+3)-(2h-15)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top